2021
DOI: 10.3390/molecules26020329
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Human Skin Penetration, Antioxidant and Antimicrobial Activity of Ethanol-Water Extract of Fireweed (Epilobium angustifolium L.)

Abstract: Epilobium angustifolium L. is applied as an antiseptic agent in the treatment of skin diseases. However, there is a lack of information on human skin penetration of active ingredients with antioxidative potential. It seems crucial because bacterial infections of skin and subcutaneous tissue are common and partly depend on oxidative stress. Therefore, we evaluated in vitro human skin penetration of fireweed ethanol-water extracts (FEEs) by determining antioxidant activity of these extracts before and after pene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 75 publications
5
45
0
Order By: Relevance
“…In our study, phenolic acids such as ChA, GA, 4-HB, 3-HB, 3,4-DHB, and CA were identified by HPLC, and GA was found in a considerable amount. Some phenolic acids, like GA, ChA, 3,4-DHB, and CA, were also found in the herbs of E. angustifolium by Zagórska-Dziok et al, Nowak et al, Ruszová et al, and Lasinskas et al [ 3 , 10 , 23 , 24 ], whereas Zagórska-Dziok et al and Shikov et al found the highest GA compared to the other phenolic acids [ 3 , 25 ]. On the other hand, a lower content of GA and ChA in E. angustifolium compared to other polyphenol compounds was identified by Jariene et al [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In our study, phenolic acids such as ChA, GA, 4-HB, 3-HB, 3,4-DHB, and CA were identified by HPLC, and GA was found in a considerable amount. Some phenolic acids, like GA, ChA, 3,4-DHB, and CA, were also found in the herbs of E. angustifolium by Zagórska-Dziok et al, Nowak et al, Ruszová et al, and Lasinskas et al [ 3 , 10 , 23 , 24 ], whereas Zagórska-Dziok et al and Shikov et al found the highest GA compared to the other phenolic acids [ 3 , 25 ]. On the other hand, a lower content of GA and ChA in E. angustifolium compared to other polyphenol compounds was identified by Jariene et al [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Marti-Mesteres et al showed high penetrations of CA through pigskin. However, these authors applied CA as a pure compound dissolved in propylene glycol at the time penetration of 72 h [ 73 ], while, in our previous studies, CA penetrated through human skin from a 70% ( v / v ) ethanol solution [ 10 ]. Ethanol is a promoter of transepidermal transport, which affects the effectiveness of active substance penetration into the skin [ 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations